Estimation of Above Ground Biomass and carbon stocks of Tectona grandis and Gmelina arborea stands in Gorontalo Province, Indonesia - YOSEP RUSLIM; Daud Sandalayuk; Rochadi Kristiningrum; Andi Sahri Alam (Society for Indonesian Biodiversity, 2021)
Abstract. Ruslim Y, Sandalayuk D, Kristiningrum R, Alam AS. 2021. Estimation of Above Ground Biomass and carbon stocks of Tectona grandis and Gmelina arborea stand in Gorontalo Province, Indonesia. Biodiversitas 22: 1497-1508. Plantation forest plays an important role to fulfill timber needs, while more recently plantation forest is increasingly acknowledged to sequester and store carbon which can mitigate climate change and also as carbon sequestration for the environment. This study aimed to calculate the stand potential, stand biomass and carbon stocks of teak (Tectona grandis) and gmelina (Gmelina arborea) stands in the context of land after being abandoned in Gorontalo Province, Indonesia. Four plots with size of one hectare each were sampled in which each species (i.e. teak and gmelina) consisted of two plots. In each plot, the diameter at the breast-high (1.3 m) and the height of each individual were recorded. Data analysis included growth parameters of the stands (i.e., Mean Annual Increment/MAI and Current Annual Increment/CAI) and above-ground biomass and carbon sequestered by the stands. Simple linear regression using polynomial trendline was used to determine the relationship between variables and the degree of the relationship. The results showed that the maximum growth of teak stands at Plots I and II reached a maximum point at the age of 32 and 25 years with the total volume of 307.50 and 254.81 m3ha-1, respectively. While the maximum growth of gmelina stands at Plots I and II reached a maximum point at the age of 15 years with the total volume of 190.54 and 251.80 m3ha-1, respectively. The biomass content in teak stands at Plots I and II and gmelina stands at Plots I and II were respectively 267.83; 221.94; 104.03 and 137.48 tons ha-1. Meanwhile, the carbon content in teak stands at Plots I and II and gmelina stands at Plots I and II were respectively 125.88; 104.31; 48.90; and 64.62 tons ha-1. The results of the regression analysis suggest that there was strong relationship between carbon sequestered and the age of the stands as well as total basal area. The results of this study suggest that Tectona grandis is more potential to be developed as plantation forest than Gmelina arborea when aiming at carbon sequestration and biomass production.